COLLOCATIONS MASTERY OF THE UNIVERSITY STUDENTS - Hamka; Eka Sustri Harida (ELITE Association Indonesia, 2019)
This study is about students‟ collocation mastery of the English Department students of IAIN Padangsidimpuan. The students‟ ability in mastering vocabulary is still low; it makes the students‟ ability also low ability in mastering collocation. This research is in quantitative types, to find out the students‟ ability in collocation mastery, 25 subjects were involved in this study. A test was administered to them to analyze the collocation selected. The result of the analysis indicated that the sixth semester students of English Department IAIN Padangsidimpuan were in low categories, and it is needed to deliberate learning and teaching. The students felt difficult to understand collocation because they need to remember it more.